If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(8 + x) + 4(x + 3) = -6 (8 * -2 + x * -2) + 4(x + 3) = -6 (-16 + -2x) + 4(x + 3) = -6 Reorder the terms: -16 + -2x + 4(3 + x) = -6 -16 + -2x + (3 * 4 + x * 4) = -6 -16 + -2x + (12 + 4x) = -6 Reorder the terms: -16 + 12 + -2x + 4x = -6 Combine like terms: -16 + 12 = -4 -4 + -2x + 4x = -6 Combine like terms: -2x + 4x = 2x -4 + 2x = -6 Solving -4 + 2x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + 2x = -6 + 4 2x = -6 + 4 Combine like terms: -6 + 4 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 5x+4(4x-17)=58 | | 10=-3(2d+4) | | 14=-x | | 17y+10y= | | 2r+9(-4+6r)= | | 3(-3)+2y=12 | | 4x-27=3x+17 | | 18x+30=156 | | -2x+11+6x-3y= | | Y=2(2)+12 | | 2(f-4)-4f=-6f+9f+4 | | 4x+2(2x)=4x(4x) | | 1.25x=21+0.5x | | 6(x-4)-2x+6=7x-4(x+6)-2 | | 5x^2=8x+21 | | 8x-1=6x-6 | | .75b-4=12 | | 3(x-5)=29 | | -9m=-45 | | 9x--5=-6 | | 4u-5=y | | 4t+1+2t-5t=5+3 | | f(a)=9(a)-5 | | 295=-6x+7(n+6) | | 6(3x+7)-12x= | | -8-2j=-j | | 8x-x-40=10x+c | | 93=-3(4-7n) | | 5(3+6p)=-18-3p | | 25*15=x | | 3(3)-3y=9 | | -16=-32 |